Identification and characterization of l-amino acid oxidase 2 gene in orange-spotted grouper (Epinephelus coioides). (July 2021) - Leu, Jiann-Horng; Tsai, Chi-Hang; Yang, Chia-Hsun; Chou, Hsin-Yiu; Wang, Hao-Ching
Abstract: Recently, l -amino acid oxidases (LAAOs) have been identified in several fish species as first-line defense molecules against bacterial infection. Here, we report the cloning and characterization of a fish LAAO gene, EcLAAO2, from orange-spotted grouper ( Epinephelus coioides ). The full-length cDNA is 3030 bp, with an ORF encoding a protein of 511 amino acids. EcLAAO2 is mainly expressed in the fin, gill, and intestine. Its expression is upregulated in several immune organs after challenge with lipopolysaccharide (LPS) and poly (I:C). The recombinant EcLAAO2 protein (rEcLAAO2), expressed and purified from a baculovirus expression system, was determined to be a glycosylated dimer. According to a hydrogen peroxide-production assay, the recombinant protein was identified as having LAAO enzyme activity with substrate preference for L-Phe and L-Trp, but not L-Lys as other known fish LAAOs. rEcLAAO2 could effectively inhibit the growth of Vibrio parahaemolyticus, Staphylococcus aureus, and Bacillus subtilis while exhibiting less effective inhibition of the growth of Escherichia coli . Finally, protein models based on sequence homology were constructed to predict the three-dimensional structure of EcLAAO2 as well as to explain the difference in substrate specificity between EcLAAO2 and other reported fish LAAOs. In conclusion, this study identifies EcLAAO2 as a novel fish LAAO with a substrate preference distinct from other known fish LAAOs and reveals that it may function against invading pathogens. Highlights: A novel l -amino acid oxidase gene, EcLAAO2, was cloned from Epinephelus coioides . LPS and poly (I:C) upregulates its expression in several immune organs. Recombinant EcLAAO2 protein purified from insect cells is a glycosylated dimer. rEcLAAO2 preferentially oxidizes L-Trp and L-Phe, and it has antibacterial activity. Fish LAAOs could be divided into two clades with different substrate specificity.